Embedding Social Care and Tolerance Character Values in Sasak Tribal Communities Through the Begawe Tradition - Sulistia Safitri; Anik Widiastuti; Poerwanti Hadi Pratiwi (Yayasan Keluarga Guru Mandiri, 2025)
The values of social care and tolerance in the Begawe tradition of the Sasak tribe are beginning to erode and have not been optimally utilized in character education. This study aims to analyze the role of the Begawe tradition in instilling values of social care and tolerance in the younger generation amid the challenges of modernization. This study employs a quantitative approach, utilizing a survey method where data are collected through questionnaires completed by respondents and analyzed descriptively. The results of the study indicate that the Begawe tradition makes a significant contribution to building a positive social character, particularly in terms of social care and tolerance, despite various challenges posed by the influence of modernization and social media, which affect the perceptions and participation of the younger generation. These findings underscore the relevance of the Begawe tradition as a powerful character-building medium within the social and cultural context of the Sasak community. This research contributes to academic knowledge by enriching character education studies through a local culture approach, particularly the Begawe tradition of the Sasak ethnic group.